2016
DOI: 10.1186/s12974-016-0695-3
|View full text |Cite
|
Sign up to set email alerts
|

Latitude and HLA-DRB1*04:05 independently influence disease severity in Japanese multiple sclerosis: a cross-sectional study

Abstract: BackgroundHigher latitude and human leukocyte antigen (HLA)-DRB1*04:05 increase susceptibility to multiple sclerosis (MS) in the Japanese population, but their effects on disease severity are unknown. We aimed to clarify the effects of latitude and the HLA-DRB1 and HLA-DPB1 genes on disease severity in Japanese patients with MS.MethodsWe enrolled 247 MS patients and 159 healthy controls (HCs) from the northernmost main island of Japan, Hokkaido Island (42–45° north), and 187 MS patients and 235 HCs from the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 49 publications
7
41
1
Order By: Relevance
“…However, there were some conflicting findings for this diagnosis. 6,7 Therefore, there was a reasonable probability that the present patient might have neuro-Behҫet's disease because of the presence of these HLA alleles. Each disease shows a different tendency of disease activity during pregnancy and puerperium.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, there were some conflicting findings for this diagnosis. 6,7 Therefore, there was a reasonable probability that the present patient might have neuro-Behҫet's disease because of the presence of these HLA alleles. Each disease shows a different tendency of disease activity during pregnancy and puerperium.…”
Section: Discussionmentioning
confidence: 80%
“…5 This effect size is much larger than the risk for MS with HLA-DRB1*15:01 or HLA-DRB1*04:05, which the present patient also possessed. 6,7 Therefore, there was a reasonable probability that the present patient might have neuro-Behҫet's disease because of the presence of these HLA alleles.…”
Section: Discussionmentioning
confidence: 80%
“…2d), both compatible with MS. 3,4 Cerebrospinal fluid was positive in oligoclonal band. Human leucocyte antigen typing revealed the presence of DRB1*04:05, which is the susceptible allele for MS. 5 Collectively, we concluded that these CNS lesions are indicative of MS. After two courses of high-dose intravenous methylprednisolone (1 g/day for three consecutive days), the lesions enhanced by gadolinium significantly diminished. However, a new small T2WI-high/diffusion weighted image-high/apparent diffusion coefficient mapping-low lesion was found in his hippocampus ( Fig.…”
Section: Editormentioning
confidence: 79%
“…19 In African Americans, HLA-DRB1 is known as the highest-risk HLA allele; however, HLA-DRB1*15:01 is present in just 6.6% of those suffering from MS. 30 HLA-DRB1*15:03 has also been reported to be associated with MS in African Americans. 30 Furthermore, in Japan, HLA-DRB1*04:05 is associated with MS. 31 The heterogeneity of the MS risk of these HLA alleles between populations might contribute to the different rates of prevalence of MS. In some studies, protective effects of HLA against MS have also been reported.…”
Section: Mhc Locus and The Hla Imputation Methodsmentioning
confidence: 98%
“…HLA‐DRB1*15:03 has also been reported to be associated with MS in African Americans . Furthermore, in Japan, HLA‐DRB1*04:05 is associated with MS . The heterogeneity of the MS risk of these HLA alleles between populations might contribute to the different rates of prevalence of MS.…”
Section: Mhc Locus and The Hla Imputation Methodsmentioning
confidence: 99%